PEMAHAMAN KARYAWAN TERHAAP MOTIVASI DAN PENGALAMAN KERJA DI HOTEL REGENT’S PARK MALANG - AP., S. Soedewo; Efendy, M. Yusuf (Manajemen & Bisnis Jurnal, 2017)
Hotel Regent's Park Malang is a company engaged in services, where businesses or services sold include room rental, restaurant, laundry and karaoke. Intense competition makes this company in demand to have employees who have high motivation and experience in work. This, however, is not balanced with co-opens, facilities, rewards, appropriate leadership. This study aims to answer the problems that have been formulated in research that is understanding the motivation and work experience that can affect employee performance, whether it is in accordance with the expected employee and company. This research is done through qualitative research method. This qualitative research approach is appropriate to apply to natural objects when the process of data analysis and information is inductive, and the findings of this qualitative research emphasize deeper meanings than general theoretical ones. The approach that is used in this research is through the approach deskrptif because the viewpoint right by the author to deepen this research. Because this method focuses on human life everyday. The data used in this study through interview techniques, observation and documentation are done directly. The subjects performed in this research are employees of Hotel Regent's Park Malang. From this research can be known and understood that the compensation, opportunity, leadership, awards and facilities is very important to note in order to achieve motivation and employee work experience that is expected by the company to service the Hotel Regent's Park Malang is improved and better